2017
DOI: 10.1089/dna.2016.3612
|View full text |Cite
|
Sign up to set email alerts
|

miR-101 Enhances Cisplatin-Induced DNA Damage Through Decreasing Nicotinamide Adenine Dinucleotide Phosphate Levels by Directly Repressing Tp53-Induced Glycolysis and Apoptosis Regulator Expression in Prostate Cancer Cells

Abstract: Tp53-induced glycolysis and apoptosis regulator (TIGAR) enhances the pentose phosphate pathway, thereby contributing directly to DNA repair due to generation of nicotinamide adenine dinucleotide phosphate (NADPH) and ribose-5-phosphate, two key precursors of DNA synthesis and repair. Targetscan database showed that miR-101 was predicted to potentially target TIGAR. Therefore, we speculated that miR-101 could enhance cisplatin-induced DNA damage by directly repressing TIGAR expression in prostate cancer cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The identified candidate miRNA was miR-101, which is linked to frizzled-4, F-box/WD repeat containing protein 11 and ubiquitin-conjugating enzyme E2 A. Previous studies have reported that miR-101 is associated with various tumor types and may regulate chemotherapeutic sensitivity in acute lymphoblastic leukemia ( 46 , 47 ). However, there have been no studies focusing on the association between miR-101 and NAFLD, to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…The identified candidate miRNA was miR-101, which is linked to frizzled-4, F-box/WD repeat containing protein 11 and ubiquitin-conjugating enzyme E2 A. Previous studies have reported that miR-101 is associated with various tumor types and may regulate chemotherapeutic sensitivity in acute lymphoblastic leukemia ( 46 , 47 ). However, there have been no studies focusing on the association between miR-101 and NAFLD, to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Later, studies further confirm that miR-101-3p targets EZH2 and suppresses proliferation and migration of PCa cells [12,13]. After thoroughly reviewing published literature on PCa, we found that ten target genes including SOD1 [14], SUB1 [15], TIGAR [16], NR2F2 [17], RLIP76 [9], COX-2 [18], Glyoxalase 1 [19], ZEB1 [20], Slug [20] as well as EZH2 [11,13,21,22] were truly inhibited by miR-101-3p in PCa tissues or cells. Furthermore, we found that the target genes of miR-101-3p were enriched in many biological processes, such as positive regulation of transcription, intracellular signal transduction, protein autophosphorylation, activation of MAPKK activity.…”
Section: Discussionmentioning
confidence: 54%
“…Among these drug-related miRNAs, miR-101 is usually downregulated in cancers. Furthermore, miR-101 is found to sensitize gastric cancer, prostate cancer, bladder cancer and hepatocellular carcinoma cells to anti-tumor drugs [ 27 , 28 , 29 , 30 ]. These reports demonstrate that miR-101 is a potential sensitizer for anti-tumor treatment.…”
Section: Discussionmentioning
confidence: 99%